2015
DOI: 10.1115/1.4031872
|View full text |Cite
|
Sign up to set email alerts
|

Implementation, Optimization, and Validation of a Nonlinear Lifting Line-Free Vortex Wake Module Within the Wind Turbine Simulation Code qblade

Abstract: The development of the next generation of large multimegawatt wind turbines presents exceptional challenges to the applied aerodynamic design tools. Because their operation is often outside the validated range of current state-of-the-art momentum balance models, there is a demand for more sophisticated, but still computationally efficient simulation methods. In contrast to the blade element momentum method (BEM), the lifting line theory (LLT) models the wake explicitly by a shedding of vortex rings. The wake m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 7 publications
0
40
0
Order By: Relevance
“…The near and far wake is modelled with vortex line elements, which are shed at the blades trailing edge during every time step and then undergo free convection 15 behind the rotor. Vortex elements are de-singularized using a cut off method (as described by Marten et al (2016)) based on the vortex core size. Viscous diffusion in the wake is accounted for through vortex core growths term.…”
Section: Numerical Methods Of Qbladementioning
confidence: 99%
“…The near and far wake is modelled with vortex line elements, which are shed at the blades trailing edge during every time step and then undergo free convection 15 behind the rotor. Vortex elements are de-singularized using a cut off method (as described by Marten et al (2016)) based on the vortex core size. Viscous diffusion in the wake is accounted for through vortex core growths term.…”
Section: Numerical Methods Of Qbladementioning
confidence: 99%
“…As the wind tunnel is short, the influence of the turbulence on the vortex breakdown might be less pronounced than in a far field case or in a longer wind tunnel. Moreover, Medici and Alfredsson (2006) showed that up to x/d = 2 the initial wakes for a case with and without free-stream turbulence are quite similar, even with a higher turbulence intensity than in the present setup. However, the blockage ratio by Medici and Alfredsson (2006) was less than 3 % and consequently much smaller than in the present case.…”
Section: Wind Tunnelmentioning
confidence: 44%
“…FVW codes have been recently used in a number of studies on the unsteady aerodynamics of FWTs. () They were found to be accurate in various conditions. Instead of lifting lines, vortex wake models have been used with lifting surfaces modeling the blades for either HAWTs or vertical axis wind turbines (VAWTs) .…”
Section: Models and Methodsmentioning
confidence: 99%